F(-3)=-7(-3)-4

Simple and best practice solution for F(-3)=-7(-3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(-3)=-7(-3)-4 equation:


Simplifying
F(-3) = -7(-3) + -4

Reorder the terms for easier multiplication:
-3F = -7(-3) + -4

Multiply -7 * -3
-3F = 21 + -4

Combine like terms: 21 + -4 = 17
-3F = 17

Solving
-3F = 17

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Divide each side by '-3'.
F = -5.666666667

Simplifying
F = -5.666666667

See similar equations:

| x^3+4x^2+9x+10=0 | | 4x^2-5=-77 | | X-14.1=2.7 | | b=3c | | 1+2u=23+u | | 23-y+2y=34 | | 4-2m=4-6m | | 2x+6y=22 | | 9u-u=40 | | F(4)=-7(4)-4 | | (x+3)+(2x-8)=28 | | 14-0.2(x-10)=0.4(25+x) | | 8v+v=54 | | 36x-3=123 | | 5x-2y+4-x-y= | | 2(6+n)=52 | | 17-6.10*/2+12= | | 164+10=14 | | 15+25=X | | -164+10=14 | | -24-3x=6-8x | | 6=7w-5w | | 17-6.10/2+12= | | 72-3x=24x+24 | | 5y+3y=8 | | 17-6.10*2+12= | | 9x-7=29 | | 112=4x | | 0.4x+3=0.8x+1 | | x^2+14x=72 | | 4(x-2)+8x=-44 | | 3/10(x-2)=3 |

Equations solver categories